2012
DOI: 10.5603/fhc.2012.0023
|View full text |Cite
|
Sign up to set email alerts
|

The concentrations of soluble HLA-G protein are elevated during mid-gestation and decreased in pre-eclampsia

Abstract: Abstract:The aim of our study was to investigate the dynamics of the alterations of soluble human leukocyte antigen-G (sHLA-G) concentrations in sera of healthy non-pregnant women, as well as healthy pregnant women and patients with pre-eclampsia. Thirty five patients with pre-eclampsia, 52 healthy pregnant women, and 24 healthy non-pregnant women were included in the study. Sera concentrations of sHLA-G protein were determined using the immunoenzymatic ELISA method. Statistical analysis was performed using AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Defective HLA-G expression has been associated with PE (82). HLA-G levels in plasma from women who subsequently develop PE are lower than control patients (83, 84). MSC have been shown to secrete and express HLA-G (73, 74).…”
Section: Molecular Mechanisms Of Msc Immunosuppressive Effectmentioning
confidence: 81%
“…Defective HLA-G expression has been associated with PE (82). HLA-G levels in plasma from women who subsequently develop PE are lower than control patients (83, 84). MSC have been shown to secrete and express HLA-G (73, 74).…”
Section: Molecular Mechanisms Of Msc Immunosuppressive Effectmentioning
confidence: 81%
“…The target of miRNA‐152 and 19a is HLA‐G, which is expressed by trophoblasts, the major physiological function of which is to protect the foetus from cytotoxicity of NK cells. HLA‐G plays an important role in immune tolerance at the feto‐maternal interface . Studies have shown that the expression of HLA‐G in the placenta in PE was significantly lower than in normal pregnancy and the downregulation of HLA‐G may result in the rejection of the foetus, poor invasion by trophoblasts and insufficient uterine artery remodelling.…”
Section: Innate Immunitymentioning
confidence: 99%
“…First, a direct association between reduced HLA-G expression in term placentas and preeclampsia has been demonstrated with in situ hybridization, immunohistochemistry on frozen sections, and with a ribonuclease protection assay ( 65 67 ). Second, circulating sHLA-G levels are decreased in preeclampsia, and in some cases this is observed as an early event in pregnancy in women who subsequently develop preeclampsia compared with women with uncomplicated pregnancy ( 62 , 64 , 68 70 ). Third, HLA-G polymorphisms have been associated with sHLA-G levels in peripheral blood from blood donors and with HLA-G protein expression in the placenta during pregnancy ( 71 , 72 ), and fourth, HLA-G polymorphisms, some of which are associated with circulating levels, are further associated with increased risk of preeclampsia in some studies ( 73 76 ) but not in all ( 77 80 ).…”
Section: Hla-g In Pregnancy and Preeclampsiamentioning
confidence: 99%